Socio-economic status of schools and university academic performance: implications for Australia’s higher education expansion - Dockery, Michael; Li, Ian (National Centre for Student Equity in Higher Education, 2014)
Data for first year university undergraduates from an Australian university are linked to schools data, to examine the impact of school characteristics, particularly socioeconomic status, on influencing university marks. School socioeconomic status is found to have moderate impacts on university performance, with students from less privileged schools performing better in university given their Australian Tertiary Admission Rank (ATAR). Prior academic achievement, as proxied by the ATAR, is found to be a strong determinant of university scores. School sector or school resourcing characteristics are found to have negligible impacts on university academic scores. Equity measures to increase university access for low socioeconomic status students and those from lower socioeconomic status schools can be expanded without compromising academic standards.